The Role Of Islamic Religious Education Teachers As Spiritual Counselors In Preventing Bullying Based On Islamic Values At Smp Negeri 1 Amuntai Utara - Diannor, Agus; Wardiah, Siti; Nor Annisa, Wafa (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The rampant occurrence of bullying behavior, specifically verbal teasing and social exclusion, at SMP Negeri 1 Amuntai Utara causes severe psychological and social impacts on studentsThis issue is viewed as a moral and spiritual deviation contradicting Islamic values. This study aims to analyze the role of Islamic Religious Education (PAI) teachers as spiritual counselors in preventing bullying and identify the application strategy of Islamic values in guiding students away from this behavior. This research employs a qualitative approach using field research (field research). Data were collected through observation, in-depth interviews, and documentation with PAI teachers, students, and school officials1. The implemented strategies include modeling good behavior (uswah hasanah), individual and group spiritual counseling, habituation of Qur'anic values, and cultivating empathy and compassion among students. The findings show that PAI teachers play a strategic role as moral and spiritual guides, utilizing the spiritual approach to foster inner moral consciousness (tazkiyah an-nafs) that bullying is a form of tyranny (zulm) that violates Islamic principles. The study concludes that PAI teachers are essential spiritual counselors in creating a religious, empathetic, and bullying-free school environment. This approach offers a significant contribution to developing Islamic guidance and counseling